Studying the Effect of Zn2SnO4 Nanoparticles on Antibacterial Activity Using the Sol-Gel Method - Kawther, Kawther; Ziad T. Khodair; Firas Mahmoud Hadi (ASJ - Academic Science Journal, 2025)
In this study, zinc stannate Zn2SnO4 (ZTO) nanoparticles were prepared using the sol-gel method. X-ray diffraction technique was used to investigate the Zn2SnO4 nanoparticles, which showed that they have a polycrystalline structure and were of the cubic type. Field emission scanning electron microscopy (FE-SEM) measurements showed that the grains were nanostructures with regular shapes, and their average atom dimensions were 162.01 nm. Transmission electron microscopy (TEM) showed the appearance of nanosheets and others resembling nanoscale tilts. Zn2SnO4 nanoparticles showed biological activity against pathogenic bacteria and showed a difference in the average diameter of inhibition for all types of used bacteria, and the average diameter of inhibition ranged from 11 to 17 mm.